Causal association between sleep traits and the risk of coronary artery disease in patients with diabetes - Tian, Mengyun; Ma, Hongchuang; Shen, Jiaxi; Hu, Teng; Cui, Hanbin; Huangfu, Ning (Frontiers in Cardiovascular Medicine, 2023)
Background and aims: The association between sleep traits and coronary artery disease (CAD) in patients with diabetes has been reported in previous observational studies. However, it remains unclear whether these potential associations are causal. The current study aimed to assess the causality between sleep traits and CAD in individuals with diabetes. Methods: Instrumental genetic variables associated with five sleep-related traits (insomnia, sleep duration, getting up, morningness and snoring) were identified from published genome-wide association studies (GWAS). Summary-level data for genetic associations with CAD were obtained from a recently published GWAS study involving 15,666 individuals with diabetes (3,968 CAD cases and 11,696 controls). The inverse variance weighting method was employed for the main analysis. Further sensitivity analysis was carried out to confirm the robustness of the research results. Results: Genetic liability to insomnia was significantly related to the high risk of CAD in individuals with diabetes (odds ratio (OR), 1.163; 95%CI, 1.072-1.254; p=0.001). The causal relationship between snoring and CAD in people with diabetes was close to being statistically signiﬁcant (OR, 1.010; 95%CI, 1.000-1.020; p=0.050). Sleep duration, getting up and morningness may not be causally related to the risk of CAD in individuals with diabetes. Similar results can be verified in most sensitivity analyses. Conclusions: We provide genetic evidence that insomnia is causally associated with a higher risk of CAD in patients with diabetes. Further research is needed to explore the relationship between the risk of CAD with other sleep characteristics. Sleep health treatments should be emphasized to prevent CAD in individuals with diabetes.